Resource assessment using a combination of seabed mounted and semi-stationary vessel-mounted ADCP measurements (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Accurate resource assessment for tidal stream sites is crucial for calculation of the Levelized Cost of Energy (LCOE) of each project or turbine. The main method as recommended by the IEC’s technical specification on tidal stream resource assessment involves using a numerical model as well as several measurements using Acoustic Doppler Current Profilers (ADCP) mounted on the seabed. Ideally, once the locations of the turbines are known precisely, seabed mounted ADCP measurements will be undertaken at all turbine locations. For large tidal arrays this is however challenging, especially with project development constrained by time and budget. The MeyGen project is the largest planned tidal stream energy project in the world, aiming to develop up to 398 MW of installed power in the Pentland Firth, Scotland, with current velocities reaching up to 5 m/s. During Phase 1 of the project, four 1.5 MW turbines were installed. During Phase 2, site characterization campaigns were carried out to plan the deployment of additional turbines, representing 28 MW of tidal power capacity. Based on learning from Phase 1 around the need to accurately calibrate numerical models at a very detailed spatial resolution, and the costs and time to obtain seabed ADCP measurements at many turbine locations, a new measurement methodology was proposed. This method used semi-stationary vessel-mounted ADCP measurements to characterize the flow at the planned turbine locations, rather than relying on a few seabed-mounted ADCP measurements and a numerical model, or relying on seabed-mounted ADCPs at all the locations of the planned turbines.This works introduces the method used for calculating the tidal stream velocities at the planned turbine locations. A 35-day seabed mounted ADCP survey was conducted as a baseline within the area of planned turbines. It used a Teledyne SentinelV50 ADCP configured with 2Hz sampling rate, 5-beam velocities and 1 m depth cells. Using harmonic analysis and prediction, the current velocities were obtained for a 18.6 years period.Additionally, during seven days of spring tide, water velocities were measured using a vessel mounted ADCP. It used a Teledyne Workhorse 600kHz configured with circa 1Hz sampling rate and 1 m depth cells. The vessel mounted measurements were undertaken at each turbine location during 5 minutes every hour, for a 12-hour tidal cycle. During each 5 minutes the vessel kept its position within 15-meter radius around the nominal position. Similar vessel-mounted measurements were also undertaken above the seabed mounted ADCP, as well as continuously for 12 hours.The semi-stationary vessel mounted ADCP measurements were validated against the seabed-mounted ADCP measurements with the co-located 12-hour data. The current velocity magnitude obtained from the vessel mounted measurements at the turbine locations were then correlated with the simultaneous data from the seabed mounted ADCP. This correlation was finally combined with the 18.6 years timeseries predicted at the seabed-mounted ADCP location to obtain long-term times series and statistics for turbine locations. The final presentation and paper will provide the results of this study.